Individuals' Unemployment Experiences: Heterogeneity and Business Cycle Effects - Adriaan S. Kalwij (Institute for the Study of Labor (IZA), 2001)
This study examines individuals? unemployment experiences from the age of 18 up to the age of 35 using a large panel of administrative records on unemployment related benefit claims of men in the United Kingdom over the past two decades. The main focus is on the extent to which individuals? unemployment experiences are affected by regional and skill differences, i.e. individual heterogeneity, and the business cycle. In particular this study analyses the extent to which repeated unemployment is experienced by individuals who are not able to get stable employment and individuals who hold several jobs interrupted with spells of unemployment before obtaining stable employment. The results provide new insights into the long-term benefits of a labour market program aimed at increasing the employability of the unemployed and getting them into work, such as the New Deal in the UK.
Keywords: E32; C41; J64; 330; Unemployment; duration model; business cycles; Arbeitslosigkeit; Dauer; Langzeitarbeitslosigkeit; Konjunktur; Humankapital; Schätzung; Großbritannien